Erythema multiforme in the dog - PAITAKI (Χ. ΠΑΪΤΑΚΗ), C.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Canine erythema multiforme is a rarely seen skin eruption that is characterized by variable clinical signs and a rather distinctive histopathology. From a clinical point of view erythema multiforme is of particular interest, mainly due to its life-threatening potential. It is considered a host-specific cell-mediated hypersensitivity reaction, leading to epidermal and follicular wall keratinocyte apoptosis. Although the exact pathomechanism is not currently fully understood, it is often associated with drugs, infections, neoplastic and connective tissue diseases, adverse food reactions and idiopathy. Definite diagnosis is based on the clinical and histopathological findings and therapy aims to the elimination of the triggering factors and the institution of supportive measures. The usefulness of glucocorticoids in canine erythema multiforme is still controversial.